Assessment of the width of attached gingiva using different methods in various age groups: A clinical study - Gouri Bhatia; Ashish Kumar; Manish Khatri; Mansi Bansal; Sameer Saxena (Wolters Kluwer Medknow Publications, 2015)
Background: The width of attached gingiva varies from tooth to tooth and also among individuals with mixed opinions regarding an "adequate" or "sufficient" dimension of the gingiva. Although the need for a so-called adequate amount of keratinized tissue for maintenance of periodontal health is questionable, the mucogingival junction serves as an important clinical landmark in periodontal evaluation. There are various methods of locating the mucogingival junction namely the functional method and the visual method with and without histochemical staining, which aid in the measurement of the width of attached gingiva. Materials and Methods: This study was carried out to assess the full mouth mid-buccal width of attached gingiva in individuals of four different age groups. This study also evaluated the difference in visual and histochemical methods in identification of the mucogingival junction to calculate the width of attached gingiva. Results: It was seen that the width of attached gingiva increases with age, and there was no significant difference in the width of attached gingiva by both the methods. Conclusion: Width of attached gingival varies in different areas of the mouth and also increases with age with no significant difference in the method of its assessment.